Rekonstruksi Kurikulum Pondok Pesantren Ahlussunnah Waljamaah Ambunten Sumenep - Bustanul Ulum (JSP: Jurnal Studi Pesantren, 2022)
This research aims to analyze the rationality of curriculum reconstruction, reconstructive design, and curricular reconstitution measures at pesantren Ahlussunnah Waljamaah, Ambunten Sumenep. This research uses a phenomenological approach, which is the theory that the reality seen at the surface level is only a symptom of what is hidden behind the inner reality of the subject. The results of this study show that the rationality of the reconstruction of the curriculum of pesantewn Ahlussunnah Waljamaah is a form of awareness of all the components of the hostel and the demands of the community by combining religious and general lessons that are included in its curricula. The aim is to improve the quality of science by transforming the values of science into a pattern of personality. Furthermore, the reconstruction design of the curriculum is the result of the rebuilding of curricula that has been carried out and is based on three main principles, namely religious ritual, scientific achievement, and willingness to live an independent life. In the final part, the steps taken by the boarding house are gradual with systematic steps. He evaluated his curriculum by looking at the mastery of the material, the effectiveness of the curricula, the achievement of the educational objectives, and the evaluation system.